2020
DOI: 10.18502/ijph.v48i11.3528
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Frameshift Mutation in Abnormal Spindle-Like Microcephaly (ASPM) Gene in an Iranian Patient with Primary Microcephaly: A Case Report

Abstract: Autosomal recessive primary microcephaly (MCPH) is a rare genetic disorder, leading to the defect of neurogenic brain development. Individuals with MCPH reveal reduced head circumference and intellectual disability. Several MCPH loci have been identified from several populations. Genetic heterogeneity of this disorder represents molecular testing challenge. An 8 yr old female, born from consanguineous parents, was attended to Fardis Central Lab, Alborz, Iran. Based on the reduced circumference and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The findings of this study are in line with previous reports because we have also observed 68.75% (22/32) families carrying a mutation in ASPM . Building on another elegant study by Letard and colleagues (Letard et al, 2018)—summarizing 189 ASPM mutations in 282 previously reported and 39 new families—we reviewed the literature published thereafter and extended the mutational spectrum to 211 in 381 families (Ahmed et al, 2019; Bazgir, Agha Gholizadeh, Sarvar, & Pakzad, 2019; Bhargav, Sreedevi, Swapna, Vivek, & Kovvali, 2017; Boonsawat et al, 2019; Khan, Wang, Han, Ahmad, & Zhang, 2018; Kvarnung et al, 2018; Li et al, 2017; Marakhonov et al, 2018; McSherry et al, 2018; Moriwaki et al, 2019; Okamoto, Kohmoto, Naruto, Masuda, & Imoto, 2018; Shaheen et al, 2019). This number also includes 10 novel mutations of 8 families identified in this study (Figure 1 and Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study are in line with previous reports because we have also observed 68.75% (22/32) families carrying a mutation in ASPM . Building on another elegant study by Letard and colleagues (Letard et al, 2018)—summarizing 189 ASPM mutations in 282 previously reported and 39 new families—we reviewed the literature published thereafter and extended the mutational spectrum to 211 in 381 families (Ahmed et al, 2019; Bazgir, Agha Gholizadeh, Sarvar, & Pakzad, 2019; Bhargav, Sreedevi, Swapna, Vivek, & Kovvali, 2017; Boonsawat et al, 2019; Khan, Wang, Han, Ahmad, & Zhang, 2018; Kvarnung et al, 2018; Li et al, 2017; Marakhonov et al, 2018; McSherry et al, 2018; Moriwaki et al, 2019; Okamoto, Kohmoto, Naruto, Masuda, & Imoto, 2018; Shaheen et al, 2019). This number also includes 10 novel mutations of 8 families identified in this study (Figure 1 and Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients may exhibit mild to severe developmental delay, sloping forehead, epilepsy, and hereditary hearing loss. Predominantly, primary microcephaly shows an autosomal recessive mode of inheritance ( 4 , 5 ). So far, mutations in 25 genes have been linked with MCPH.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The overall incidence of microcephaly at birth varies from 1.3 to 150/100 000 in different worldwide populations. 4 Microcephaly is predominantly autosomal recessive (AR) and is therefore more prevalent in consanguineous unions than other family structures. 3,4 However, families with either autosomal dominant or X linked inheritance have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…4 Microcephaly is predominantly autosomal recessive (AR) and is therefore more prevalent in consanguineous unions than other family structures. 3,4 However, families with either autosomal dominant or X linked inheritance have been reported. 5,6 Other clinical features associated with microcephaly are delayed motor and cognitive development, intellectual disability, movement disorders, feeding and vision problems, epilepsy, and autism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation